Analysis of Students' Creative Thinking Using the Project-Based Learning Model in Colloids - Nurfatmasari, Nova; Fitriah, Dewi Lailatul; Yusbarina, Yusbarina; Kurniawati, Yenni; Fatisa, Yuni (Journal of The Indonesian Society of Integrated Chemistry, 2026)
This study aims to describe the profile of students’ creative thinking skills following the implementation of the Project-Based Learning (PjBL) model on the topic of colloids. The research employed a descriptive method with a one-shot case study design. The participants were 33 eleventh-grade students from 11th Grade MIPA 4 at State Senior High School 1 Pekanbaru. Data were collected using validated essay test instruments and structured observation sheets. The results indicated that students’ creative thinking skills based on the essay test reached 56.18% (moderate category), while the observation results during the learning process reached 77.17% (good category). An analysis of the creative thinking indicators revealed that the fluency aspect achieved 71.21%, originality 52.62%, elaboration 48.47%, and flexibility 45.85%. A similar pattern was observed in the observation data, where fluency obtained the highest score, followed by originality and elaboration. However, the flexibility aspect remains in the lowest category compared to the other indicators, both in the essay test and observation results. These findings imply that although the PjBL model effectively stimulates idea fluency and originality, more targeted instructional interventions are needed to enhance students’ cognitive flexibility in solving complex chemistry problems